(untitled) (Andamios, Revista de Investigación Social, 2011)
A specific moment of the Bogota’s history is assessed through the analysis of a homicide, when the white, stately (“señorial”) colonial order meets a crisis because of the emergence of new social classes, specifically the urban proletariat and its women. The article shows how the narrative of the homicide is used by the aristocratic elite to represent the ghost that scares them; producing fear about it, but it is also showed how this specter can generate processes of resistance against the modern/colonial order.